Hubungan Perilaku Sedentari terhadap Nilai Tekanan Darah pada Mahasiswa - Destira, Fellycia; Mariani, Mariani (Fakultas Kedokteran Universitas Sriwijaya, 2021)
The proportion of Indonesian population with a sedentary behavior of more than equal to 6 hours/day is 24.1%. The negative effects that can be caused by sedentary behavior is high blood pressure. This can be occur because sedentary behavior can give a systemic effect on vascular, metabolic and autonomic. The purpose of this study was to determine the association between sedentary behavior and blood pressure values. This is an analytic study with a cross-sectional study approach that conducted from July-September 2019 on 107 respondents with ages ranging from 16-22 years. Data on gender, sedentary behavior, and blood pressure values ​​obtained through the Bouchard’s Physical Activity Record questionnaire and sphygmomanometer were analyzed using the chi-square method. Meanwhile, data on mean duration of sedentary physical activity and blood pressure values ​​were analyzed using the independent samples t-test method. The results showed that there was a significant association between gender and blood pressure values (p = 0,000), sedentary physical activities such as watching TV (p = 0.001), playing laptop (p = 0,000), sitting playing phone (p = 0.001), sitting in transportation (p = 0.004), learning (p = 0.038), driving (p = 0.003), and a significant association between the sedentary behavior with blood pressure values ​​(p = 0.001) with OR = 6.981. The conclusions of this study shows that sedentary behavior is a risk factor for increased blood pressure values.